2004
DOI: 10.1111/j.1478-4408.2004.tb00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different preparation and dyeing processes on the physical strength of the Ingeo† fibre component in an Ingeo fibre/cotton blend. Part 1; Scouring followed by dyeing with disperse and reactive dyes‡

Abstract: A study has been conducted to examine the effect of different preparation and dyeing processes on the physical strength of the Ingeo fibre component of an Ingeo fibre/cotton blend. An alkaline scouring process (for the cotton), followed by a two‐bath, two‐stage dyeing process in which the Ingeo fibre underwent a simulated dyeing with disperse dyes, followed by the cotton being dyed with reactive dyes, caused minimal deterioration to the strength of the Ingeo fibre. However, it is considered that problems might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 3 publications
2
26
0
1
Order By: Relevance
“…It is thus apparent that significant degradation is brought about by the routine processes associated with dyeing. A similar trend was reported by Phillips et al 43,44 who observed the Mn of PLA fabric to fall significantly as a result of dyeing at 110 C for 30 min at pH 5.0. They further noted that dyeing at higher temperatures and/or for longer times exacerbated the problem, as might be anticipated.…”
Section: Stage IIsupporting
confidence: 88%
“…It is thus apparent that significant degradation is brought about by the routine processes associated with dyeing. A similar trend was reported by Phillips et al 43,44 who observed the Mn of PLA fabric to fall significantly as a result of dyeing at 110 C for 30 min at pH 5.0. They further noted that dyeing at higher temperatures and/or for longer times exacerbated the problem, as might be anticipated.…”
Section: Stage IIsupporting
confidence: 88%
“…The effect of preparation and dyeing processes on the strength of PLA contained in the PLA/cotton blend was investigated and it was illustrated that these processes did weaken the PLA fiber but its retained strength after processing was in a commercially acceptable level. However, dyeing PLA/cotton using 1-bath, all-in process with Kayacelon React dyes under neutral conditions at 110 o C did ruin the strength of PLA beyond acceptability (Phillips et al, 2004a(Phillips et al, , 2004c. This experience suggests that the use of higher temperatures or longer times of dyeing can cause degradation of the polymer, an observation confirmed by Kameoka et al (1997) who claimed that the temperature, time and pH of dyeing resulted in a significant reduction in the molecular weight of the polymer.…”
Section: Dyeing Pla Fiber With Disperse Dyesmentioning
confidence: 95%
“…The dyeing properties of PLA have been investigated, especially in comparison with PET fiber. The dyeing of 100% PLA fiber has been intensively studied (Scheyer & Chiweshe, 1999;Nakamura et al, 2001;Phillips et al, 2003Phillips et al, , 2004aPhillips et al, , 2004bPhillips et al, , 2004c. Owing to its relatively hydrophobic nature like PET, PLA can normally be dyed with disperse dyes.…”
Section: Dyeing Pla Fiber With Disperse Dyesmentioning
confidence: 99%
“…However, it has been pointed out that prolonged dyeing time particularly at alkaline or neutral conditions may result in significant damage to PLA (Phillips et al, 2004b).…”
Section: Dyeing Pla Blendsmentioning
confidence: 99%